ORGANIZATIONAL AND ECONOMIC FOUNDATIONS OF SOCIO-ECONOMIC DEVELOPMENT OF TOURISM IN THE CARPATHIAN REGION - DANYLO, Yaroslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article explores the comprehensive development of regions in Ukraine with a special focus on the tourism sector, considered through the prism of state regional policy. Based on the analysis of tourism as a fusion of natural resources and tourist attractiveness, including the integration of several adjacent areas, we examine the tourism potential of individual areas and territorial communities. According to the Law of Ukraine "On the Principles of State Regional Policy", state regional policy is defined as a system of measures aimed at improving the quality of life based on the rational use of resources and the cultural uniqueness of the regions. The study of state regional policy reflects the strategic integration of the tourism industry as a fundamental aspect of regional development, emphasizing the effective use of natural and cultural resources. The development of organizational and economic principles to support and develop the tourism sector in the context of state policy is proposed. Mechanisms for interregional integration and cooperation that will promote synergy and regional-level tourism development are suggested. Special attention is paid to the need to create comprehensive programs and projects that will support the sustainable use of tourism resources and promote cultural and economic growth. Practical recommendations for forming an effective regional policy are outlined, including the development of synergistic management models that optimize interaction between different elements of the tourism infrastructure. It is determined that creating organizational conditions for the integration of the tourism potential and resources of various regions can significantly enhance their competitiveness and attractiveness. Strategic directions and mechanisms for improving regional policy in the field of tourism are developed, considering current trends and challenges. A significant contribution has been made to the study of the problems of comprehensive development of regional tourism, providing a new perspective on opportunities and strategies for optimizing tourism activities in the context of state policy.
Keywords: regional innovation potential; tourism; intellectual capital; foreign investment; investment processes; management; strategy; digitalization; entrepreneurial activity; tourist enterprises; region; development; strategic planning; competitiveness; crisis; globalization